Eddy kinetic energy variability of the Kuroshio Extension and its upstream-downstream connectivity - Lee, SeungYong; Na, Hanna; Park, Young-Gyu; Park, Hyung-Ju; Cho, Suna (Frontiers in Marine Science, 2025)
The Kuroshio Extension (KE) system in the western North Pacific includes energetic meanders of the Kuroshio jet that are full of mesoscale eddies. This study analyzed the variability of eddy kinetic energy (EKE) in the KE region, focusing on its connectivity between the upstream and downstream regions. Three dominant modes of the EKE variability were identified through the empirical orthogonal function (EOF) analysis during 1993–2014, using a high-resolution reanalysis product. The spatial patterns of both the first and third modes present an overall out-of-phase relationship between the upstream and downstream regions. The principal component (PC) time series of the first EOF mode exhibits interannual to decadal variability and is correlated to the North Pacific Gyre Oscillations index with a time lag of about three years. It is also correlated with the PC time series of the third mode with a two-year time lag, suggesting that the third mode precedes the first mode associated with the westward propagation of baroclinic Rossby waves. The second mode, however, shows an in-phase spatial pattern between the upstream and downstream, and its PC time series exhibits strong seasonal variability with an interannual modulation. It is concluded that the upstream-downstream connectivity of the EKE in the KE region is explained by a combination of the out-of-phase variability on interannual to decadal timescales and the in-phase variability on seasonal to interannual timescales.